KOMPETENSI, BUDAYA ORGANISASI DAN KINERJA PEGAWAI - Febri Yuliani, Asparida, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Competence, Organizational Culture and Employee Performance. This research uses a descriptive quantitative research method approach. The purpose of this study is to determine the competence, organizational culture and employee performance. Direct data collection techniques through questionnaires to the State civil apparatus in the District of Rumbai, amounting to 56 people and secondary data obtained from the district of Rumbai. Data analysis uses product moment regression correlation. The results showed that the performance variable of the employees of the Rumbai district of Pekanbaru in the good category, from the four performance indicators it could be seen that the highest indicator was the quantity and cooperation built by the employees in working for the community. Based on the results of the analysis it can be seen that the influence of organizational competence and culture on the performance of the employees of the Rumbai district of Pekanbaru City simultaneously has a significant effect and partially also has a significant effect, which can be seen that the influence of organizational culture is greater when compared to employee competency.